Comparative Study of the Sedative and Anti-nociceptive Effects of Sacrococcygeal Epidural Administration of Romifidine, Lidocaine, and Romifidine/Lidocaine in the Dromedary Camel - Marzok, Mohamed; Almubarak, Adel I.; Abdel-Raheem, Sherief M.; El-khodery, Sabry; Shawaf, Turke; Kandeel, Mahmoud (Frontiers in Veterinary Science, 2022)
In a randomized prospective study, comparative sedative and anti-nociceptive effects of epidural administration of romifidine (RO), lidocaine (LD), and a combination of romifidine-lidocaine (ROLD) in camel were evaluated. Eighteen healthy adult dromedary camels were assigned randomly to three treatment groups (n = 6), each receiving 50 μg/kg of RO, 0.30 mg/kg of LD, or a combination of both RO and LD. All treatments were expanded in 0.9% sterile normal saline solution to a final dose volume of 20 ml and administered directly into the sacrococcygeal space. After epidural injection of each treatment, the onset time, duration, anatomical extension of anti-nociception, and sedation were documented. Anti-nociception was tested at different areas using a pinprick test and artery forceps pinching at the perineum and inguinal area. RO and ROLD treatments resulted in mild to severe sedation and complete bilateral analgesia with loss of sensation in the tail, perineum, scrotum in males, vulva in females, the caudal aspect skin of the upper hind limb, and inguinal region (udder in females and the prepuce in males). The anatomic extent of anti-nociception reached the chest cranially and the footpad distally. Camels who received LD showed the shortest duration (P < 0.001) to the onset of perineal anti-nociception (3.67 ± 0.33 min) followed by those who received RO LD (4.00 ± 0.37 min) and RO (6.67 ± 0.33 min), respectively. RO and ROLD resulted in significantly (P < 0.001) longer periods of analgesia (158.33 ± 4.01 min and 165 ± 3.87 min, respectively) than LD (75.83 ± 3.27). An epidural RO and ROLD would appear to produce a very effective and acceptable anti-nociceptive effect in the perineal and inguinal regions of camels.